Zahar Mohra (Bezoar) an Alexipharmic Unani Mineral Drug: Review - Mustehasan; Azhar, Misbahuddin; Naushin, Sofia; Alam, Mahe (Journal of Drug Delivery and Therapeutics, 2020)
Rhazes (855-925 AD) the great scholar of Unani System Medicine (USM), initially classified Materia Medica according to animal, mineral and plant origin. Zahar Mohra is a Greenish white, good‑looking mineral stone with a slippery feel having a good smell and taste obtained from mines. In USM it is considered to be a universal antidote. The great Unani Scholar Yuhannā Māsawayh (777-857 AD), was one of the first physicians who mentioned the medicinal uses of Zahar Mohra. In Unani Medicine it is used to treat epidemic diseases such as Haiza (Cholera), Tawoon (Plague), as an antidote for different poisoning and to provide strength to vital organs. To check adulteration the quality standard of Zahar Mohra has been laid down. All the available information regarding this historically important stone has been compiled which will help the researcher to find a solution of pandemic disease in the current scenario. Key words: Zahar Mohra, Unani Medicine, Fade Zahar Kani, Mineral Bezoar